2007
DOI: 10.1176/appi.ps.58.9.1181
|View full text |Cite
|
Sign up to set email alerts
|

Needs for and Barriers to Correctional Mental Health Services: Inmate Perceptions

Abstract: Results of this study provide an overarching conceptualization of barriers hindering inmates' willingness to seek services, as well as the types of problems for which they are likely to seek services. Also, inmates' mental health treatment history affected their current perceptions of services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 0 publications
3
39
0
Order By: Relevance
“…The recent recognition of the need for mental health professionals to treat co-occurring issues of mental illness and criminalness (Draine, Salzer, Culhane, & Hadley, 2002; Hodgins et al, 2007; Morgan, Fisher, et al 2010; Morgan, Steffan, Shaw, & Wilson, 2007) in conjunction with federal mandates that correctional systems are obligated to provide mental health services that meet inmates’ health care needs, highlights the necessity that treatment development emphasize the co-occurring issues of mental illness and criminalness. In fact, from this comprehensive review, only two studies targeted dual issues of mental illness and criminalness.…”
Section: Discussionmentioning
confidence: 99%
“…The recent recognition of the need for mental health professionals to treat co-occurring issues of mental illness and criminalness (Draine, Salzer, Culhane, & Hadley, 2002; Hodgins et al, 2007; Morgan, Fisher, et al 2010; Morgan, Steffan, Shaw, & Wilson, 2007) in conjunction with federal mandates that correctional systems are obligated to provide mental health services that meet inmates’ health care needs, highlights the necessity that treatment development emphasize the co-occurring issues of mental illness and criminalness. In fact, from this comprehensive review, only two studies targeted dual issues of mental illness and criminalness.…”
Section: Discussionmentioning
confidence: 99%
“…The recent recognition of the need for mental health professionals to treat co-occurring issues of mental illness and criminalness (Draine, Salzer, Culhane, & Hadley, 2002;Hodgins et al, 2007;Morgan, Fisher, et al 2010;Morgan, Steffan, Shaw, & Wilson, 2007) in conjunction with federal mandates that correctional systems are obligated to provide mental health services that meet inmates' health care needs, highlights the necessity that treatment development emphasize the co-occurring issues of mental illness and criminalness. In fact, from this comprehensive review, only two studies targeted dual issues of mental illness and criminalness.…”
Section: Discussionmentioning
confidence: 99%
“…Medical Self Reliance Previous research has found that self-reliant attitudes are associated with lower use of specialty mental health services (Ortega and Alegria 2002;Morgan et al 2007). People who prefer to solve health problems on their own are less likely to use formal medical care.…”
Section: Mental Healthcare Service Utilization and Ethnicitymentioning
confidence: 99%